The use of accounting policy options under IFRS in Europe: Do country, industry, and topic factors matter? - Karsten Eisenschmidt; Joanna Krasodomska (Contemporary Economics, 2021)
Since the formation of the International Accounting Standards Board (IASB), the use of International Financial Reporting Standards (IFRS) has spread and they have become global standards for financial reporting. However, they are not used unanimously all over the world. This paper focuses on differences in countries' approaches to IFRS. Our study aims to investigate the use of accounting policy choice for selected options in Europe with a particular focus on countries, industry and topic-specific firm factors. We analyze financial statements of 416 companies of the STOXX Europe 600 operating in 17 European countries. We use content analysis to identify the companies' decisions to choose a particular option allowed under IFRS and run a logistic regression to identify potential factors that influence them. Our findings suggest that the factors under investigation do not always have a significant influence on the accounting option choice. However, the country variables seem to have a stronger influence than industry or topic variables. The study contributes to the body of literature mainly because it investigates a uniform European setting with the use of the 2017 data and it covers countries not included in previous studies. Its results also provide a basis for discussion on the fi-nancial statements quality and the impact of IFRS across countries.
Keywords: M41; M48; 330; Accounting choice; IFRS; international differences; Europe; accounting harmonization